DEVELOPMENT OF ALGORITHM OF PLANNING OF INCREASE OF COMPETITIVENESS OF AUTO REPAIR BUSINESSES - Remzi Ablaev; Tatiana Cocodei; Julia Antokhina (Вестник Северо-Кавказского федерального университета)
Car and vehicle service market of Russia is enough large, growing up and highly competitive. Thus evaluation of competitiveness and estimation of ways for its growth are important practices for every car service firms. In this article questions of improvement of organizational and methodical aspects of cheduling of increase in competitiveness of the car repair enterprise are considered. The authors offered a technique of definition of set of actions for development offactors of competitiveness of car service firms and their quantitative parameters taking into account a ratio of these indexes with the leading competitor and the existing economic, technological restrictions of this firm. Main methods used in this study are system approach, methods of the logical, economic analysis and a standard mathematical apparatus of the linear programming. The received result allows to maximize an increase of complex assessment of competitiveness and is a basis of scheduling of strategic development of car and vehicle service firm.